Presence of Bacillus Cereus from Local Unhusked (Rough) Rice Samples in Sarawak, Malaysia - Lesley Maurice, Bilung; Feven, Tesfamariam; Rowena, Andriesse; Yeo, Freddy Kuok San; Chong, Yeeling; Ahmad Syatir, Tahar (Penerbit UMT, 2018)
Bacillus cereus is a widespread endospore forming pathogen that can cause diarrhoeal and emetic food poisoning. The purpose of this study was to determine the occurrence of B. cereus from local unhusked (rough) rice. A total 24 local unhusked (rough) rice samples were collected from various locations in Sarawak, Malaysia. The analysis was carried out using the most probable number–polymerase chain reaction (MPN–PCR) method. The bacterial loads of B. cereus in all samples were found to be more than 1100 MPN/g. PCR analysis showed that all the samples were positive for B. cereus. The finding of this study suggests that the local unhusked rice can be one of the potential sources for B. cereus foodborne outbreak. This study can be used as a baseline data for future risk assessment of B. cereus in local food sources.